Measuring the Mayor's Political Commitment and Opportunities for Developing Tuberculosis Elimination Policies in Makassar City - Andi surahman Batara; Ella Andayanie (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
ntroduction: Tuberculosis is globally one of the ten biggest causes of death in the world, around 10.6 million new cases and 1.3 million deaths in 2022. Indonesia ranks second in the world in the list of countries with a high tuberculosis burden. There are 19,071 cases of tuberculosis sufferers in South Sulawesi. Makassar City ranks first, namely 9,157 cases of tuberculosis found throughout 2023. The purpose of the study was to emphasize its dual focus on assessing political commitment and policy opportunities. Method: The research design used is quasi-qualitative research and the Mayor of Makassar is the key informant. The data collection technique uses the PCOM-RAT (Political Commitment and Opportunity Measurement-Rapid Assessment Test) survey questionnaire and is continued with in-depth interviews with informants. Result: Measurement of political commitment using the PCOM-RAT questionnaire is divided into three parts, namely verbal commitment, institutional commitment, and budget commitment. The assessment score for the political commitment of the Mayor of Makassar shows good political commitment, with a total political commitment score of 18. Opportunities for developing TB policies can be understood based on three streams, namely problem stream, policy stream, and political stream. The overall assessment score shows that Makassar City has had a high opportunity for developing TB policies, with a total score of 29. Conclusion: The Mayor of Makassar has a high political commitment in the TB elimination policy in Makassar City. High political commitment from a Regional Head is an opportunity for the success of implementing a program. Political commitment is the desire to act and continue to act until the job is done. A leader who has a high political commitment to tuberculosis will resolve the tuberculosis problem until it is finished. Furthermore, the opportunity to develop a TB elimination policy in Makassar City is also high. The TB elimination policy can be developed by paying attention to increasing the capacity of health workers in case finding, improving the quality of TB screening and diagnosis, improving the treatment monitoring system, encouraging community participation by strengthening collaboration between stakeholders, and also encouraging research to improve TB control capabilities.